Determination of formation constants and structural characterization of cyclodextrin inclusion complexes with two phenolic isomers: carvacrol and thymol - Kfoury, Miriana; Landy, David; Ruellan, Steven; Auezova, Lizette; Greige-Gerges, Hélène; Fourmentin, Sophie (Beilstein Journal of Organic Chemistry, 2016)
Carvacrol and thymol have been widely studied for their ability to control food spoilage and to extend shelf-life of food products due to their antimicrobial and antioxidant activities. However, they suffer from poor aqueous solubility and pronounced flavoring ability that limit their application in food systems. These drawbacks could be surpassed by encapsulation in cyclodextrins (CDs). Applications of their inclusion complexes with CDs were reported without investigating the inclusion phenomenon in deep. In this study, inclusion complexes were characterized in terms of formation constants (Kf), complexation efficiency (CE), CD:guest molar ratio and increase in bulk formulation by using an UV–visible competitive method, phase solubility studies as well as 1H and DOSY 1H NMR titration experiments. For the first time, a new algorithmic treatment that combines the chemical shifts and diffusion coefficients variations for all guest protons was applied to calculate Kf. The position of the hydroxy group in carvacrol and thymol did not affect the stoichiometry of the inclusion complexes but led to a different binding stability with CDs. 2D ROESY NMR experiments were also performed to prove the encapsulation and illustrate the stable 3D conformation of the inclusion complexes. The structural investigation was accomplished with molecular modeling studies. Finally, the radical scavenging activity of carvacrol and thymol was evaluated by the ABTS radical scavenging assay. An improvement of this activity was observed upon encapsulation. Taken together, these results evidence that the encapsulation in CDs could be valuable for applications of carvacrol and thymol in food.
Keywords: cyclodextrins; DOSY-NMR; formation constant; molecular modeling; solubility

(untitled) - Llana-Ruiz-Cabello, M.; Pichardo, S.; Maisanaba, S.; Puerto, M.; Prieto, A. I.; Gutiérrez-Praena, D.; Jos, A.; Cameán, A. M. (Food Chem. Toxicol., 2015)

(untitled) - Hyldgaard, M.; Mygind, T.; Meyer, R. L. (Front. Microbiol., 2012)

(untitled) - Zotti, M.; Colaianna, M.; Morgese, M. G.; Tucci, P.; Schiavone, S.; Avato, P.; Trabace, L. (Molecules, 2013)

(untitled) - Burt, S. (Int. J. Food Microbiol., 2004)

(untitled) - Chavan, P. S.; Tupe, S. G. (Food Control, 2014)

(untitled) - Zheng, L.; Bae, Y. M.; Jung, K. S.; Heu, S.; Lee, S. Y. (Food Control, 2013)

(untitled) - Gutiérrez, L.; Escudero, A.; Batlle, R.; Nerín, C. (J. Agric. Food Chem., 2009)

(untitled) - Kuorwel, K. K.; Cran, M. J.; Sonneveld, K.; Miltz, J.; Bigger, S. W. (Packag. Technol. Sci., 2014)

(untitled) - Klein, G.; Rüben, C.; Upmann, M. (Curr. Microbiol., 2013)

(untitled) - Suntres, Z. E.; Coccimiglio, J.; Alipour, M. (Crit. Rev. Food Sci. Nutr., 2015)

(untitled) - Brewer, M. S. (Compr. Rev. Food Sci. Food Saf., 2011)

(untitled) - Quiroga, P. R.; Asensio, C. M.; Nepote, V. (J. Sci. Food Agric., 2015)

(untitled) - Grice, H. C. (Food Chem. Toxicol., 1988)

(untitled) - Witschi, H. P. (Food Chem. Toxicol., 1986)

(untitled) - Mastelić, J.; Jerković, I.; Blažević, I.; Poljak-Blaži, M.; Borović, S.; Ivančić-Baće, I.; Smrěcki, V.; Žarković, N.; Brčić-Kostic, K.; Vikić-Topić, D.; Müller, N. (J. Agric. Food Chem., 2008)

(untitled) - Locci, E.; Lai, S.; Piras, A.; Marongiu, B.; Lai, A. (Chem. Biodiversity, 2004)

(untitled) - Kfoury, M.; Auezova, L.; Ruellan, S.; Greige-Gerges, H.; Fourmentin, S. (Carbohydr. Polym., 2015)

(untitled) - Kfoury, M.; Landy, D.; Auezova, L.; Greige-Gerges, H.; Fourmentin, S. (Beilstein J. Org. Chem., 2014)

(untitled) - Marques, H. M. C. (Flavour Fragrance J., 2010)

(untitled) - Szente, L.; Szejtli, J. (Trends Food Sci. Technol., 2004)

(untitled) - Szejtli, J. (Chem. Rev., 1998)

(untitled) - Del Valle, E. M. M. (Process Biochem., 2004)

(untitled) - Szente, L.; Szejtli, J. (Adv. Drug Delivery Rev., 1999)

(untitled) - Schmidt, B. V. K. J.; Hetzer, M.; Ritter, H.; Barner-Kowollik, C. (Prog. Polym. Sci., 2014)

(untitled) - Bethanis, K.; Tzamalis, P.; Tsorteki, F.; Kokkinou, A.; Christoforides, E.; Mentzafos, D. (J. Inclusion Phenom. Macrocyclic Chem., 2013)

(untitled) - Guimarães, A. G.; Oliveira, M. A.; Alves, R. D. S.; Menezes, P. D. P.; Serafini, M. R.; De Souza Araújo, A. A.; Bezerra, D. P.; Quintans, L. J. (Chem.-Biol. Interact., 2015)

(untitled) - Kamimura, J. A.; Santos, E. H.; Hill, L. E.; Gomes, C. L. (LWT–Food Sci. Technol., 2014)

(untitled) - Kfoury, M.; Auezova, L.; Fourmentin, S.; Greige-Gerges, H. (J. Inclusion Phenom. Macrocyclic Chem., 2014)

(untitled) - Miguel, M. G.; Dandlen, S. A.; Figueiredo, A. C.; Pedro, L. G.; Barroso, J. G.; Marques, M. H. (Acta Hortic., 2010)

(untitled) - Mulinacci, N.; Melani, F.; Vincieri, F. F.; Mazzi, G.; Romani, A. (Int. J. Pharm., 1996)

(untitled) - Nieddu, M.; Rassu, G.; Boatto, G.; Bosi, P.; Trevisi, P.; Giunchedi, P.; Carta, A.; Gavini, E. (Carbohydr. Polym., 2014)

(untitled) - Santos, E. H.; Kamimura, J. A.; Hill, L. E.; Gomes, C. L. (LWT–Food Sci. Technol., 2015)

(untitled) - Tao, F.; Hill, L. E.; Peng, Y.; Gomes, C. L. (LWT–Food Sci. Technol., 2014)

(untitled) - Caron, L.; Tilloy, S.; Monflier, E.; Wieruszeski, J.-M.; Lippens, G.; Landy, D.; Fourmentin, S.; Surpateanu, G. (J. Inclusion Phenom. Macrocyclic Chem., 2000)

(untitled) - Decock, G.; Fourmentin, S.; Surpateanu, G. G.; Landy, D.; Decock, P.; Surpateanu, G. (Supramol. Chem., 2006)

(untitled) - Ciobanu, A.; Landy, D.; Fourmentin, S. (Food Res. Int., 2013)

(untitled) - Fourmentin, S.; Ciobanu, A.; Landy, D.; Wenz, G. (Beilstein J. Org. Chem., 2013)

(untitled) - Loftsson, T.; Hreinsdóttir, D.; Másson, M. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Kurkov, S. V.; Loftsson, T. (Int. J. Pharm., 2013)

(untitled) - Kfoury, M.; Auezova, L.; Greige-Gerges, H.; Ruellan, S.; Fourmentin, S. (Food Chem., 2014)

(untitled) - Schneider, H. J.; Hacket, F.; Rüdiger, V.; Ikeda, H. (Chem. Rev., 1998)

(untitled) - Mura, P. (J. Pharm. Biomed. Anal., 2014)

(untitled) - Fernandes, C. M.; Carvalho, R. A.; Pereira da Costa, S.; Veiga, F. J. B. (Eur. J. Pharm. Sci., 2003)

(untitled) - Sun, D.-Z.; Li, L.; Qiu, X.-M.; Liu, F.; Yin, B.-L. (Int. J. Pharm., 2006)

(untitled) - Ribeiro, L.; Carvalho, R. A.; Ferreira, D. C.; Veiga, F. J. B. (Eur. J. Pharm. Sci., 2005)

(untitled) - Djedaini, F.; Sheng Zhao, L.; Perly, B.; Wouessidjewe, D. (J. Pharm. Sci., 1990)

(untitled) - Chen, M.; Diao, G.; Zhang, E. (Chemosphere, 2006)

(untitled) - Veiga, F. J. B.; Fernandes, C. M.; Carvalho, R. A.; Geraldes, C. F. G. C. (Chem. Pharm. Bull., 2001)

(untitled) - Jullian, C.; Miranda, S.; Zapata-Torres, G.; Mendizábal, F.; Olea-Azar, C. (Bioorg. Med. Chem., 2007)

(untitled) - Srinivasan, K. (Crit. Rev. Food Sci. Nutr., 2014)

(untitled) - Lucas-Abellán, C.; Mercader-Ros, M. T.; Zafrilla, M. P.; Gabaldón, J. A.; Núñez-Delicado, E. (Food Chem. Toxicol., 2011)

(untitled) - Li, S.; Yue, J.; Zhou, W.; Li, L. (J. Inclusion Phenom. Macrocyclic Chem., 2015)

(untitled) - Gharibzahedi, S. M. T.; Razavi, S. H.; Mousavi, M. (Carbohydr. Polym., 2014)

(untitled) - Chakraborty, S.; Basu, S.; Lahiri, A.; Basak, S. (J. Mol. Struct., 2010)

(untitled) - López-Nicolás, J. M.; Pérez-López, A. J.; Carbonell-Barrachina, Á.; García-Carmona, F. (J. Agric. Food Chem., 2007)

Advances in Analytical Chemistry and Instrumentation - Higuchi, T.; Connors, A. K. (Phase-Solubility Techniques, 1965)